The Analysis of Pronunciation Challenges of EFL Students in Senior High School: Causes and Solutions - Nafi’a, Ilma; Salsabila, Bilkis; Munawaroh, Badriyatul; El-Sulukiyyah, Ana Ahsana; Chuquin, Ector Geovanny Pupiales (Indonesian Journal of Multidisciplinary Educational Research, 2025)
This study examines common pronunciation errors in English diphthong, specifically /aʊ/ and /aɪ/, among tenth-grade AKL students at SMK PGRI 4 Pasuruan. It analyzes the causes of the mispronunciation errors and strategies to tackle the challenges. The qualitative descriptive method was employed, with data collected through observations from students reading a narrative fable titled Mouse and a semi-structured interview.  The analysis identified frequent errors, including simplifying diphthongs into single vowels or substituting them with incorrect diphthongs, caused by first-language interference and limited exposure to authentic English pronunciation. The intervention was conducted in two sessions. In the first session, students read the fable aloud, and pronunciation errors were identified and addressed through guided practice. The second session involved reviewing recordings of their initial readings, comparing them with native speaker examples, and practicing in groups to improve accuracy. Targeted phonetic interventions significantly improved students' pronunciation accuracy and confidence. The study highlights the importance of structured, phonetic-focused activities in enhancing English pronunciation among non-native learners.